Minerals Beneficiation - The Design and Calibration of a Faraday Pail for Measuring Charge Density of Mineral Grains - James E. Lawver; James L. Wright (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
This paper discusses the design and calibration of a Faraday pail for measuring electric charge. The paper also shows that at least for two minerals, quartz and calcite, the phenomenon that Johnson termed "reversibility" can be explained in terms of the contact electrification between the minerals and the metal rotor of an electrostatic machine. Each year the free world produces about 13 million tons of mineral concentrates by electrical separation. However, despite the rather general acceptance of electrical concentration as an industrial process, research in this area has lagged far behind the efforts devoted to competitive processes such as froth flotation. The purpose of this paper is to describe the design and calibration of a Faraday ice pail for measuring charge density on mineral grains and to show some of its applications in the area of electrostatic and electrodynamic research. THE DESIGN AND CALIBRATION OF FARADAY PAILS FOR ABSOLUTE CHARGE MEASUREMENT The electric charge on mineral grains at a given time during an electrical concentration process is de- pendent on many factors and cannot, in general, be accurately calculated a priori. It is thus important to devise a method of measuring absolute charge. One method of measuring electric charge is to note the potential rise of an electrometer when charged particles drop into a Faraday pail. Two types of Faraday pail have been constructed and calibrated. The first type, Faraday Pail I (Fig. 1), is a vertical pail originally designed to measure the charge due to contact electrification between mineral grains and a metal rotor or due to conductive induction when mineral grains are passed over a rotating cylinder in the presence of an electric field. The second type, labeled Faraday Pail II (Fig. 2), is a horizontal pail designed to determine the charge distribution of mineral grains after they pass through the separating zone of the electrical concentrator shown in Fig. 4. The main advantage of the horizontal pail is its low head-room requirement and the long opening which enables the experimenter to sample the entire width of the stream of minerals being separated. The Faraday pails were calibrated in the following manner: A calibration head was constructed in the form of a hollow brass sphere that could be held in an insulated metal cylinder by vacuum (Fig. 1). The capacitance of the sphere was calculated by measuring the capacitance of the sphere and cylinder combined and that of the cylinder alone and subtracting the latter measurement from the former. The sphere was then charged to a known potential (V) and allowed to drop into the Faraday pail which was attached to a Keithley Model 610A electrometer. This instrument has an accuracy of 2% full scale and has